FENOMENA KOMUNIKASI MULTIKULTURAL DI KOTA AMBON (Studi Pengalaman Komunikasi Antara Etnik Bugis dan Etnik Ambon) - Andi Fitriyani (DIALEKTIKA, 2020)
ABSTRACT In communicating often encountered an event where we have difficulty communicating with others who have different background. This happens because of differences in regional backgrounds with different cultural structures. This writing aims to determine the experience of communication between ethnic Bugis and ethnic Ambon in Ambon city and Factors that support and inhibit the behavior of inter-ethnic communication Bugis and ethnic Ambon. The method used is qualitative descriptive. The results showed that communication between ethnic Bugis with ethnic Ambon in the city of Ambon already bias achieve mutual understanding. Factors that support and inhibit in the process of communication can also be used as a tool to achieve a common understanding, which led to the attitude of tolerance between them. Keywords: Inter-ethnic communication, Bugis, Ambon